2019
DOI: 10.1161/atvbaha.118.311942
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Deficiency Alters the Survival of Ly-6C lo Monocytes in ApoE −/− Mice and Reduces Early-Stage Atherosclerosis—Brief Report

Abstract: Objective— To determine the role of microRNA-21 (miR-21) on the homeostasis of monocyte subsets and on atherosclerosis development in ApoE −/− (apolipoprotein E) mice. Approach and Results— In ApoE −/− mice, miR-21 expression was increased in circulating Ly-6C lo nonclassical monocytes in comparison t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Previous studies have confirmed that miR-21 in endothelial cells is significantly increased in atherosclerotic plaques and that it causes pharmacological effects by directly targeting the PTEN tumor suppressor gene, indicating a pivotal effect of the miR-21/PTEN pathway in atherosclerosis (24,25). A number of reports have indicated that the miR-21/PTEN pathway regulates important functions of Ecs, apoptosis and inflammatory responses during atherosclerosis (26,27). However, the exact actions of the miR-21/PTEN pathway in the progression of atherosclerosis and in the cardioprotection of geniposide remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that miR-21 in endothelial cells is significantly increased in atherosclerotic plaques and that it causes pharmacological effects by directly targeting the PTEN tumor suppressor gene, indicating a pivotal effect of the miR-21/PTEN pathway in atherosclerosis (24,25). A number of reports have indicated that the miR-21/PTEN pathway regulates important functions of Ecs, apoptosis and inflammatory responses during atherosclerosis (26,27). However, the exact actions of the miR-21/PTEN pathway in the progression of atherosclerosis and in the cardioprotection of geniposide remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the group of Stéphane Potteaux identified an miRNA critical for generating Ly6C low monocytes. The authors observed increased expression of miR-21 in non-classical Ly6C low monocytes of atherosclerotic ApoE −/− mice, which mediated their higher number and lifespan in this model (59). The frequency of Ly6C low monocytes in blood, bone marrow and spleen was markedly reduced in ApoE −/− miR-21–deficient mice.…”
Section: Role Of Mirnas In Monocyte Subsetsmentioning
confidence: 99%
“…In vivo, miR-21 knockout alters the homeostasis of Ly-6C lo cells and reduces the formation of early atherosclerotic lesions in apolipoprotein E knockout mice (26), while in low-density lipoprotein receptor knockout mice, miR-21 knockout leads to inflammatory cell accumulation, defects in efferocytosis and accelerated development of advanced atherosclerosis (25). Furthermore, miR-21 knockout exacerbates angiotensin II-induced thoracic aortic aneurysm and dissection formation in mice, which may be associated with the TGF-β/SMAD3 signaling pathway (27).…”
Section: Genistein Alleviates Chronic Vascular Inflammatory Response mentioning
confidence: 99%